Decay of the total variation and Hardy norms of solutions to parabolic conservation laws - Schonbek, M; Suli, E (Unspecified, 1998)
We study the decay of solutions to parabolic conservation laws in the Hardy space $\cal H$$^{1}$ and in the total variation norm. We show that solutions to scalar equations and systems decay to zero without a rate in $\cal H$$^{1}$, and that the total variation of solutions decays to zero at an algebraic rate.